(3fRgI GdbdhH hGdNhGWQ HHYV eG JQcg GdChGFd ddChGNQs - (3CHh GdeMGSf eMeO Hf YHO GdhgGH Hf TYHGf Hf OGhhO GdgePGfj GdcGXej,J (B1303 (3g` s
(3ChdgG (B:s
(3GeG HYO ajbhd GdeaJbQ Edi QMeI QHg GdhOhO eMeO Hf YHOGdhgGH GdgePGfi GdeYQha Hjf CUMGHg HGHf OGhO s
(3BNQgG (B:s
(3cdeG cGf ef GdPfH dfG Hge GdQMef GQL ZaQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(386) s
Keywords: (3abg GdePGgH GdCNQis